Territorial communication plan: Model and examples to disseminate academic research (based on the theme of the 2030 Agenda) - Fernandes, Roberto Mauro da Silva (Seven Editora, 2024)
The research carried out by universities is of paramount importance for the development of society, the studies help in the creation of social technologies that can be fundamental for the progress of contemporary societies. However, just conducting research is not enough, it is necessary to take it to different audiences. It is necessary for the researcher to use different means and strategies of dissemination and to mix the traditional means with the new information technologies typical of the twenty-first century. In this way, the objective of this discussion is to present a model (with examples) of a plan for scientific dissemination and academic communication based on hypothetical research whose theme is the 2030 Agenda, it is a territorial Communication Plan. DOI:https://doi.org/10.56238/sevened2024.014-029